Yoghurt Sinbiotik Berbasis Probiotik Lokal Dapat Mencegah Diare dan Mengubah Status Hematologi Tikus (SYNBIOTIC YOGHURT BASED ON INDIGENOUS PROBIOTIC: IT’S EFFECT ON DIARRHEA AND HEMATOLOGICAL STATUS IN RATS) - Astawan, Made; Wresdiyati, Tutik; ., Suliantari; Nababan, Yenni MS (Jurnal Veteriner, 2013)
The objective of this study was to observe the effect of functional synbiotics yoghurt (made ofindigenous probiotic + oligofructosaccharides) in rats that were infected with Enteropathogenic Escherichiacoli (EPEC), and to detect its effect on hematological status. A total of 25 male Sprague Dawley rats wereused in this study and divided into five treatment groups: (i) negative-control; (ii) positive-control; (iii)synbiotic yoghurt; (iv) synbiotic yoghurt + EPEC; and (v) conventional prebiotic yoghurt. Yoghurt (109 cfu/mL lactic acid bacteria) was given orally using feeding tube at day one until day 4. At day 8 – day 14animals were infected with EPEC (107 cfu/mL) orally using feeding tube; at day 22 blood samples werecollected for hematology analysis (erythrocytes, hematocrit (Hct), hemoglobulin (Hb), platelets, andleucocytes). Post infection with the EPEC diarrhea was developed in rats both in the control positivegroups and in the synbiotic yoghurt + EPEC group. Animals in the positive-control group had a significantlyhigher thrombocytes and leucocytes counts and Hct compared to that in animals in the other groups(P<0.01). Whereas there were no significant effect on the erythrocytes counts and Hb (P>0.05). The treatmentwith synbiotic yoghurt, in both synbiotic yoghurt only and synbiotic yoghurt + EPEC groups significantlyreduced the platelets and leucocytes counts and Hct of rats
Keywords: synbiotic yoghurt, EPEC, hematology